Proceedings of the Seventh International Conference on Information and Communication Technologies and Development 2015
DOI: 10.1145/2737856.2737883
|View full text |Cite
|
Sign up to set email alerts
|

Promoting participatory community building in refugee camps with mapping technology

Abstract: Mapping technology has the potential to be a helpful tool in community building. This paper explores its promise for this purpose in refugee camps. We posit such tools when used for participatory planning can be useful for building more sustainable living environments. This is especially true when a camp is transitioning from a site of crisis response into a stable location of recovery. In this note, we first discuss the current state of refugee camps and then examine the benefits and constraints of mapping te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(25 citation statements)
references
References 7 publications
1
24
0
Order By: Relevance
“…In general, the current research with refugees on community building is in its exploratory phase [60]. To our knowledge, there are few studies on the e ects of digital artifacts in refugee community building, especially with quanti able measurements.…”
Section: Ictd With Refugeesmentioning
confidence: 99%
See 1 more Smart Citation
“…In general, the current research with refugees on community building is in its exploratory phase [60]. To our knowledge, there are few studies on the e ects of digital artifacts in refugee community building, especially with quanti able measurements.…”
Section: Ictd With Refugeesmentioning
confidence: 99%
“…With the refugee crises extending in duration across the globe, organizations in the host countries of refugees increasingly take on bo om-up community approaches in the development of refugees' livelihoods [1,60]. Humanitarian service providers are seeking sustainable approaches to engage the a ected population in building new lives.…”
Section: Introductionmentioning
confidence: 99%
“…Although Baranoff et al. [5] found that newly settled refugees in the United States (in 2014) mostly used feature phones, by contrast, Ying et al showed that over a similar period Syrian refugees, settled in Jordanian camps, are using smartphones both to communicate with each other and to access Facebook for camp updates [38]. Several platforms aim to increase engagement of refugees and their access to information, with the majority of these targeting specifically younger refugees.…”
Section: Related Workmentioning
confidence: 99%
“…Furthermore, the potential wide range of technology literacy should also be considered [26]. However, despite a small number of isolated case studies [4,38], refugees' existing technology capacities, health experiences and knowledge have been largely under-explored, and antenatal health of refugees in particular presents a new area of research in HCI and digital health research communities. Some inspiration can be drawn for designs for refugee health from other resource constrained settings, such as work done in developing countries with marginalized communities.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation